2012
DOI: 10.1002/aic.13742
|View full text |Cite
|
Sign up to set email alerts
|

Understanding temperature dependency of hydrogen solubility in ionic liquids, including experimental data in [bmim][Tf2N]

Abstract: Previously unavailable high‐pressure solubility data of hydrogen in 1‐butyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)amide has been measured experimentally up to temperatures and pressures of 450 K and 15 MPa, respectively. In contrast to CO2 solubility, H2 tends to dissolve better in the ionic liquid at higher temperatures. This “inverse” temperature effect has been studied from a thermodynamic perspective and the underlying reason for this effect is explained. It is shown that the negative P‐T slope i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…It should be noticed that we do not report the solubility data of H 2 in ILs at low temperatures in this work, because H 2 solubility exhibits a so‐called “inverse” temperature effect . In contrast to CO and CO 2 solubility, H 2 solubility tends to decrease at low temperatures.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…It should be noticed that we do not report the solubility data of H 2 in ILs at low temperatures in this work, because H 2 solubility exhibits a so‐called “inverse” temperature effect . In contrast to CO and CO 2 solubility, H 2 solubility tends to decrease at low temperatures.…”
Section: Methodsmentioning
confidence: 85%
“…Unfortunately, although the literature contains a huge number of solubility data of CO 2 in ILs, even including data collected at low temperatures down to 228 K, the solubility data of CO or H 2 in ILs are very limited, involving approximately 200 and 600 data points for IL‐CO and IL‐H 2 systems, respectively. Furthermore, no solubility data for CO or H 2 in ILs at low temperatures (below 273.2 K) have been reported thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The similar trends were also found for 1-butyl-3-methylimidazolium bis (trifluoromethylsulfonyl)imide ([C 4 MIM][Tf 2 N])-gas systems. 33,34 The reason for the difference on temperature dependency of gas solubility will be discussed below. In addition, the solubility data predicted by COSMO-RS model using COSMOtherm X software are also listed in Supporting Information Tables S3-S5, and the results indicated that the predicted accuracy of COSMO-RS model is worse than that of UNIFAC-Lei model, especially for CO-IL systems.…”
Section: Solubility and Selectivity Of Gases In [C N Mim][x]mentioning
confidence: 99%
“…The increase in hydrogen solubility with temperature over wide temperature ranges has been observed previously for solutions of H 2 in many solvents, 41 including creosote, 42 water, 43 methanol, 44 toluene, 45 ionic liquids, 46 and PDMS. 10 In general it is thought that that the primary factors responsible for this behavior are small intermolecular forces between hydrogen and the solvent, and the decrease in solvent density with increasing temperature may increase the solubility.…”
Section: Energy and Fuelsmentioning
confidence: 71%